Clinical Characteristics and Progression of Osteogenesis Imperfecta Type III: A Case Series - Edbert Wielim; Chyntia; Regina Suriadi; I Wayan Bikin Suryawan (HM Publisher, 2025)
Background: Osteogenesis imperfecta (OI) is a rare genetic disorder primarily affecting bone formation, leading to increased bone fragility and fractures. OI Type III is characterized by severe clinical manifestations, including multiple fractures, skeletal deformities, and short stature. This case series describes the clinical characteristics and progression of three patients diagnosed with OI Type III, highlighting the impact of early intervention with zoledronic acid on their outcomes. Case presentation: This study presents three cases of OI Type III in female patients. Two patients (Patient A and Patient R) were diagnosed at birth with multiple fractures and received zoledronic acid treatment starting at three months of age. The third patient (Patient D) presented with fractures later in infancy and began treatment at one year of age. All patients demonstrated hallmark features of OI Type III, including blue sclerae, short stature, and progressive skeletal deformities. However, the two patients who received earlier treatment with zoledronic acid showed better mobility and fewer fractures compared to the patients who started treatment later. Conclusion: This case series emphasizes the importance of early diagnosis and intervention in OI Type III. Zoledronic acid appears to be effective in reducing fracture rates and improving mobility in these patients. Further studies with larger sample sizes are needed to confirm these findings and optimize treatment strategies for OI Type III.